Research Reports on Assessment of Handwriting Ability in Children Aged 6-12 Years by Using Smart Handwriting Analysis Recognition Platform - HAN Ping; YANG Wenyi; XIE Yiyang; XIE Qiurong; WANG Jiawei; YANG Caihong; ZHAN Shiqi; YAN Zhaoshan; ZHANG Yu (康复学报)
ObjectiveBy computerized analysis of writing ability assessment data, to accurately assess the quality and proficiency of writing among primary school students, and to provide data support for accurate screening and assessment of those with writing difficulties.MethodsA cross-sectional study was conducted to evaluate the writing ability of 1 085 students from grade 1 to grade 6 in the Experimental Primary School Affiliated to Minjiang Teachers College, Fuzhou, Fujian Province, using the smart handwriting analysis recognition platform (SHARP). The assessment indicators included writing speed, writing control, writing integration, time-on-paper ratio, accuracy of writing outcomes, and overall writing performance.ResultsGirls outperformed boys in writing control, writing integration, time-on-paper ratio, accuracy of writing outcomes, and overall writing performance (P<0.05). Right-handers were superior to left-handers in three indicators: writing integration, time-on-paper ratio, and overall writing performance (P<0.05). The development trend of primary school students' writing abilities: 1) In terms of writing speed, there was an overall trend of gradual acceleration in grades 1 to 6. As the grades increased, the writing speed gradually accelerated between adjacent grades of grades 1 to 4 (P<0.05), and between grades 5 and 6 (P<0.05), but the increase in writing speed between grades 4 and 5 showed no significant difference (P>0.05). 2) In terms of writing control ability, the overall trend of grades 1 to 6 showed a gradual development, with the performance of writing control ability in grade 3 being better than that in grade 2 (P<0.05), and the performance of writing control ability in grade 5 being better than that in grade 4 (P<0.05), and there was no statistical significance between the other adjacent grades (P>0.05). 3) In terms of the writing integration ability and time-on-paper ratio, as the grades increased, the higher grades developed better than the lower grades between adjacent grades 1 to 4 (P<0.05), and the difference between grades 4 to 5 and 5 to 6 was not statistically significant (P>0.05). 4) in terms of the accuracy of writing outcomes, grade 2 was better than grade 1 (P<0.05), and grade 4 was better than grade 3 (P<0.05), and there was no statistically significant difference between the other adjacent grades (P>0.05); 5) In terms of overall writing performance, grade 2 performed better than grade 1 (P<0.05), and the differences between other adjacent grades were not statistically significant (P>0.05). There was a significant negative correlation between writing control, writing integration and writing outcome accuracy and overall writing performance (r>-0.5), a highly positive correlation between time-on-paper ratio and overall writing performance (r=0.575), and a highly negative correlation between time-on-paper ratio and writing integration (r=-0.999). Writing outcome accuracy explained only 39.1% of the variation in overall writing performance, and writing outcome accuracy, time-on-paper ratio, writing control, and writing integration together explained 71.8% of the variation in overall writing performance.ConclusionAt the primary level, girls generally outperform boys in writing ability, but sex and dominant hand still do not predict overall performance in writing. As the grades increase, students' writing abilities tend to mature. Writing speed reaches a plateau around grades 4-5, writing control develops more rapidly in grades 2-3 and 4-5, and writing integration and time-on-paper ratio enters a relative stable plateau after about grade 4. Accuracy of writing outcomes alone is not suitable as a predictor of overall writing performance; writing control, writing integration, and time-on-paper ratio have strong effects on overall writing performance and can be combined as predictors of overall writing performance.